NON-DENTAL GLASS FIBER IMPACT ON TENSILE STRENGTH OF FIBER REINFORCED ACRYLIC RESIN IN DENTURE BASE - eko Hadianto; Muhammad Dian Firdausy (Jurnal Medali, 2022)
Background: Acrylic resin is a dental material that is often used because it is easy to apply and has good aesthetics. One type of acrylic resin used for denture base materials in dentistry is Heat Cured Acrylic Resin (HCAR). HCAR as base for dentures also has disadvantages including low tensile strength. Therefore, fiber can be added to heat cured acrylic resin as a reinforcing material (FRAR). This study aims to determine the effect of the addition of non-dental glass fiber on the tensile strength of HCAR.Method: This is a true experimental research using posttest only control group design. Divided into two groups, the first one is HCAR without the addition of non-dental glass fiber, the second group is HCAR with the addition of non-dental glass fiber. The data are tested using the Independent T-Test parametric test.Result: The average tensile strength of the HCAR without Non Dental Glass Fiber was 46.5169 MPa, while the average tensile strength of HCAR with the addition of Non Dental Glass Fiber was 60.3269 MPa. The independent test results show p value of = 0.000Conclusion: It was found that heat cured acrylic resin with the addition of non-dental glass fiber has a higher tensile strength than heat cured acrylic resin without the addition of non-dental glass fiber which could be used as an alternative choice in applications in dentistry.